Musculoskeletal Fitness Measures Are Not Created Equal: An Assessment of School Children in Corpus Christi, Texas - Toyin Ajisafe; Theresa Garcia; Hsin-Chen Fanchiang (Frontiers Media S.A., 2018)
This study investigated current obesity prevalence and associations between musculoskeletal fitness test scores and the odds of being underweight, overweight, or obese compared to having a healthy weight in elementary school children in Corpus Christi, Texas. The sample analyzed consisted of 492 public elementary school children between kindergarten and fifth grade. Their ages ranged from 5 to 11 years. Trunk lift, 90° push-up, curl-up, and back saver sit and reach tests were administered. Weight status was determined using BMI scores and the CDC growth charts. Obesity prevalence remains high among elementary school-aged children in Corpus Christi, Texas. Higher 90° push-up test scores were most consistently associated with decreased odds of being obese as compared to being overweight and having healthy weight except in kindergarten. Conversely, higher trunk lift test scores were associated with increased odds of being obese in second and fourth grades. When children achieved the minimum score to be classified in the Healthy Fitness Zone, those with healthy weight had similarly low musculoskeletal fitness (i.e., abdominal strength and endurance, hamstring flexibility, and trunk extensor strength and flexibility) as peers with overweight and obesity, especially in the lower grades. It was concluded that increased obesity prevalence in higher grades may be precipitated (at least in part) by low musculoskeletal fitness in the lower grades, especially kindergarten. Given previous associations in the literature, low musculoskeletal fitness may be symptomatic of poor motor skill competence in the current sample. These findings suggest a need for early and focused school-based interventions that leverage both known and novel strategies to combat pediatric obesity in Corpus Christi.